2017
DOI: 10.28992/ijsam.v1i1.22
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development Goals and Information and Communication Technologies

Abstract: Abstract:The Sustainable Development Goals (SDGs) are a wide range of global sustainable development targets for the environment, society and economy and they were launched by the United Nations in 2015. In launching the SDGs, the United Nations called on all member states to embrace what are an ambitious and demanding set of challenges but it also emphasised the vital role that businesses, would have to play if these challenges were to be met. The aim of this preliminary commentary paper is to review a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 15 publications
2
58
0
8
Order By: Relevance
“…These results support the research (Jo & Harjoto, 2011). The frequency intensity of board of commissioners' meetings can increasingly address corporate governance reforms by improving and realizing social responsibility as part of sustainability innovation (Jones et al, 2017) by optimizing media and CSR reporting methods.…”
Section: Resultssupporting
confidence: 80%
“…These results support the research (Jo & Harjoto, 2011). The frequency intensity of board of commissioners' meetings can increasingly address corporate governance reforms by improving and realizing social responsibility as part of sustainability innovation (Jones et al, 2017) by optimizing media and CSR reporting methods.…”
Section: Resultssupporting
confidence: 80%
“…This is because Carbon Management System is a veritable tool for sustainable development. A number of companies see sustainable development as capable of offering a wide range of emerging business opportunities and as such are creating or redesigning their business models (Jones et al, 2017). The study showed that firms with a quality Carbon Management System in place achieve better carbon mitigation, because it can lead to both tangible and intangible outcomes.…”
Section: Resultsmentioning
confidence: 85%
“…Table 1 provides some examples of ICTand non-ICT-oriented organizations. Both use sustainability strategies that not only minimize their environmental impact, but also increase their business opportunities, business competitiveness, and business benefits [6,7]. In particular, non-ICT-oriented organizations should look at the "big picture" of their rapidly changing external environments (EEs) and draft policies accordingly [8].…”
Section: Introductionmentioning
confidence: 99%
“…This involves organization-wide strategizing that may far exceed functional thinking or the functional perspective. Strategic organizational transformation holistically addresses the opportunities and risks posed by advanced IT to the organization, and can have major structural effects on the whole business [6,[32][33][34]. The transformation process is complex, chaotic, As previously discussed, each of the above is an example of how non-ICT-oriented organizations can develop and evolve their dynamic capabilities (DCs) to help guide their decisions and actions in their rapidly changing complex environments and sustain a competitive advantage [3,4,25] However, a key question concerning their vision, culture, organizational structure, and model of sustainable development has yet to be answered: What role can and should IT departments play in non-ICT-oriented organizations undergoing digital transformation?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation